Temperature and concentration dependences of specific heat of Bi₁-xSbx solid solutions - Rogacheva, E.I.; Doroshenko, A.N.; Nashchekina, O.N. (Functional Materials, 2018)
For Bi₁-xSbx solid solutions, the concentration (x = 0 - 0.12) and temperature (170-525 K) dependences of specific heat Cp were obtained. At all temperatures studied, three peaks of Cp were observed near x = 0.015, x = 0.037, and x = 0.07. The observed effects were attributed to critical phenomena accompanying the second-order phase transitions: percolation transition from dilute to concentrated solid solutions, the transition to a gapless state, and the semimetal-semiconductor transition, respectively. It was shown that the values of critical indexes (α = 0.11±0.01) are the same not only for different peaks but also for different temperatures and correspond to the values theoretically calculated within the framework of scale-invariant theory for three-dimensional (3D) models.